Soil in the environment : crucible of terrestrial life - Hillel, Daniel (Amsterdam ; Boston : Elsevier/Academic Press, 2008)
"Soil in the Environment provides fundamental knowledge regarding the role of the soil as a central link in the chain of domains and processes comprising the terrestrial environment, a topic that must be an essential component of every curriculum in the environmental sciences. In this book, Dr. Daniel Hillel reveals how the soil interacts dynamically with the atmosphere above and the lithosphere below, how it influences the planet's climate and hydrological cycle, how it serves as the primary habitat for a community of living organisms, and how it affects the fate of humanity." "This text offers an encompassing perspective regarding the soil's impact on the environment by organizing chapters among the three main sets of interacting processes: Physical, Chemical, and Biological. As a primary source for students and professors of soil science, ecology, forestry, hydrology, geophysics, geography and all environmental sciences, this is the definitive book for understanding the vast impact of soil."--BOOK JACKET.
Keywords: Soils -- Environmental aspects